UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) PADA MATA PELAJARAN FIKIH DI MTSS ASY-SYARIF - Dona Meliza; Fenny Ayu Monia; Muhammad Rahmat (KOLONI, 2023)
This research was conducted with the aim of describing efforts to increase learning motivation for class VIII in fiqh subjects using the Team Games Tournament (TGT) learning model at MTSS Asy-Syarif Sidang Koto Laweh, Kec. Tilatang Kamang, Kab. Agam. This research uses a qualitative approach to the class action type, the subjects of this research are 57 class VIII MTSS Asy-Syarif Sidang Koto Laweh students. Data collection was carried out by carrying out classroom actions and observation. Based on data analysis, student learning motivation shows an increase. Where children whose motivation to learn is low appear lazy in class, after implementing the TGT model their enthusiasm for learning increases. The data analysis techniques used are data reduction, display and drawing conclusions. Based on the research results, it can be concluded that the use of the Team Games Tournament learning model can increase students' learning motivation in Fiqh subjects.